ANALISIS PENGARUH VISUAL MERCHANDISING, SALES PROMOTION, DAN HEDONIC MOTIVES TERHADAP IMPULSIVE BUYING PADA RETAIL STORE ALFAMIDI GKB GRESIK - ACHMAD AFIF (Jurnal Manajerial, 2018)
The purpose of this study was to determine and analyze the effect of partial and simultaneous visual merchandising, sales promotion, and hedonic motives for impulsive purchases at Alfamidi GKB Gresik retail outlets. Sampling was carried out using nonprobability sampling technique which was used as incidental sampling by distributing 100 respondents. The analytical instrument used is to use multiple linear regression using CSS / Windows. V. 20. Testing hypotheses using t test and F test with a significant level of 5%. The calculation results show that the three variables included in the same analysis have a significant effect on impulsive purchases at Alfamidi GKB Gresik retail outlets. This conclusion is based on the results of calculations showing the calculated F value of 7.901 is greater than F table of 2.699. These three variables, it turns out the sales promotion has a significantly greater influence with a value of t 2.511 with a significant level of 0, 025%. Based on the analysis of impulsive purchases at Alfamidi GKB Gresik retail outlets, it was very dominantly influenced by sales promotions. From three variables, sales promotion must be further enhanced so that consumers carry out impulsive buying activities at Alfamidi GKB retail stores.